Unveiling hidden threats: Polycyclic aromatic hydrocarbons pollution in the glacial waters of the Meili Snow Mountains in the southeastern Tibetan Plateau - Xinyu Wen; Huawei Zhang; Hucai Zhang; Guangchao Liang; Binbin Ren; Wei Peng; Yan Yao; Mengshu Zhu (PLoS ONE, 2025)
Polycyclic aromatic hydrocarbons (PAHs) have posed considerable threats to both ecosystems and human health. To explore their characteristics and risks in temperate glacial watersheds, water samples from the Meili Snow Mountains in the southeastern Tibetan Plateau were collected and analyzed. The results revealed that the concentrations of total PAHs (∑PAHs) ranged from 406.5 to 820.9 ng‧L−1, and the mean ∑PAH level was relatively high compared to other global studies. PAHs were characterized by low–molecular–weight congeners, mainly including fluorene, and phenanthrene. Fluorene, phenanthrene, pyrene, and benzo[a]pyrene, were prevalent throughout the Meili Snow Mountains, with concentrations ranging from 164 to 425 ng‧L−1, 23.6 to 201 ng‧L−1, 17.9 to 90.1 ng‧L−1, and 50–117 ng‧L−1, respectively. PAHs originated from heterogeneous combustion sources, such as coal combustion, vehicular emissions, and biomass burning. These variations were attributed to various factors, including altitude effects, long–range atmospheric transport, and local environmental driving patterns. Specifically, ∑PAHs in runoff rivers decreased with increasing altitude, reflecting differences in local anthropogenic activities. The risk assessment indicated that PAHs posed moderate to high ecological risks and potential carcinogenic threats. This study provides valuable insights into the safety of drinking surface water resources and the structural and functional stability of ecosystem in the Meili Snow Mountains, which is significant for improving regional ecological safety and human health.